2020
DOI: 10.1101/2020.05.22.109900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Broad-spectrum virucidal activity of bacterial secreted lipases against flaviviruses, SARS-CoV-2 and other enveloped viruses

Abstract: Viruses are the major aetiological agents of acute and chronic severe human diseases that place a tremendous burden on global public health and economy; however, for most viruses, effective prophylactics and therapeutics are lacking, in particular, broad-spectrum antiviral agents. Herein, we identified 2 secreted bacterial lipases from a Chromobacterium bacterium, named Chromobacterium antiviral effector-1 (CbAE-1) and CbAE-2, with a broad-spectrum virucidal activity against dengue virus (DENV), Zika virus (ZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It can be assumed as a starting point, therefore, that the enveloped emerging/re-emerging viruses listed in Table 1 should be readily inactivated by a variety of formulated microbicidal actives. This assumption has, in fact, been verified by extensive empirical data ( Klein & Deforest, 1983 ; Sattar et al, 1989 ; McDonnell & Russell, 1999 ; Rabenau et al, 2005 ; Sattar, 2007 ; Ijaz & Rubino, 2008 ; Geller, Varbanov & Duval, 2012 ; Cook et al, 2015 , 2016 ; Cutts et al, 2018 , 2019 , 2020 ; Weber et al, 2019 ; Chin et al, 2020 ; Ijaz et al, 2020 ; Kampf et al, 2020 ; O’Donnell et al, 2020 ; Vaughan et al, 2020 ; Yu et al, 2020 ; Castaño et al, 2020 ), and has been embraced by the U.S. Environmental Protection Agency ( United States Environmental Protection Agency, 2016 ). The data for various members of the Coronaviridae family, reviewed recently by Kampf et al (2020) , Cimolai (2020) , and Golin, Choi & Ghahary (2020) support the expectation that SARS-CoV-2 and other coronaviruses of concern (e.g., MERS-CoV, SARS-CoV, mouse hepatitis virus, porcine epidemic diarrhea virus, etc.)…”
Section: Hierarchy Of Susceptibility Of Pathogens Including Sars-cov-mentioning
confidence: 81%
See 1 more Smart Citation
“…It can be assumed as a starting point, therefore, that the enveloped emerging/re-emerging viruses listed in Table 1 should be readily inactivated by a variety of formulated microbicidal actives. This assumption has, in fact, been verified by extensive empirical data ( Klein & Deforest, 1983 ; Sattar et al, 1989 ; McDonnell & Russell, 1999 ; Rabenau et al, 2005 ; Sattar, 2007 ; Ijaz & Rubino, 2008 ; Geller, Varbanov & Duval, 2012 ; Cook et al, 2015 , 2016 ; Cutts et al, 2018 , 2019 , 2020 ; Weber et al, 2019 ; Chin et al, 2020 ; Ijaz et al, 2020 ; Kampf et al, 2020 ; O’Donnell et al, 2020 ; Vaughan et al, 2020 ; Yu et al, 2020 ; Castaño et al, 2020 ), and has been embraced by the U.S. Environmental Protection Agency ( United States Environmental Protection Agency, 2016 ). The data for various members of the Coronaviridae family, reviewed recently by Kampf et al (2020) , Cimolai (2020) , and Golin, Choi & Ghahary (2020) support the expectation that SARS-CoV-2 and other coronaviruses of concern (e.g., MERS-CoV, SARS-CoV, mouse hepatitis virus, porcine epidemic diarrhea virus, etc.)…”
Section: Hierarchy Of Susceptibility Of Pathogens Including Sars-cov-mentioning
confidence: 81%
“…Small, non-enveloped viruses are considered to be less susceptible to microbicides, although these viruses display increased susceptibility to high pH, oxidizers such as sodium hypochlorite, activated hydrogen peroxide, alcohols, and a variety of microbicidal actives, relative to spores and protozoan cysts/oocysts. Mycobacteria, fungi, vegetative bacteria, and enveloped viruses appear to be more susceptible to certain formulated microbicides, such as alcohols, oxidizers, quaternary ammonium compounds (QAC), and phenolics (e.g., p -chloro- m -xylenol (PCMX)) ( Klein & Deforest, 1983 ; Sattar et al, 1989 ; McDonnell & Russell, 1999 ; Rabenau et al, 2005 ; Sattar, 2007 ; Ijaz & Rubino, 2008 ; Geller, Varbanov & Duval, 2012 ; Maillard, Sattar & Pinto, 2013 ; Cook et al, 2015 , 2016 ; Cutts et al, 2018 , 2019 , 2020 ; Rutala et al, 2019 ; Weber et al, 2019 ; Chin et al, 2020 ; Kampf et al, 2020 ; O’Donnell et al, 2020 ; Senghore et al, 2020 ; Vaughan et al, 2020 ; Yu et al, 2020 ). A number of commercially available formulated microbicides (antiseptic liquid, hand sanitizers, liquid hand wash, bar soap, surface cleanser, disinfectant wipe, and disinfectant spray) have been evaluated for virucidal efficacy against SARS-CoV-2 ( Ijaz et al, 2020 ), and as expected, were found to cause complete inactivation (3.0–4.7 log 10 ) within the 1–5 min contact times tested.…”
Section: Hierarchy Of Susceptibility Of Pathogens Including Sars-cov-mentioning
confidence: 99%
“…It can be assumed as a starting point, therefore, that the enveloped emerging/re-emerging viruses listed in Table 1 should be readily inactivated by a variety of formulated microbicidal actives. This assumption has, in fact, been verified by extensive empirical data (Klein and Deforest, 1983;Sattar et al, 1989;McDonnell and Russell, 1999;Rabenau et al, 2005;Sattar 2007;Ijaz and Rubino, 2008;Geller et al, 2012;Cook et al, 2015;Cook et al, 2016;Cutts et al, 2018Cutts et al, , 2019Cutts et al, , 2020Weber et al, 2019;Chin et al, 2020;Kampf et al, 2020;O'Donnell et al, 2020;O'Donnell et al, 2020;Vaughan et al, 2020;Yu et al, 2020;Castaño et al, 2020), and has been embraced by the U.S. Environmental Protection Agency (U.S. EPA, 2016). The data for various members of the Coronaviridae family, reviewed recently by Kampf et al (2020), Cimolai (2020), and Golin et al (2020) support the expectation that SARS-CoV-2 and other coronaviruses of concern (e.g., MERS-CoV, SARS-CoV, mouse hepatitis virus, porcine epidemic diarrhea virus, etc.)…”
Section: Hierarchy Of Susceptibility Of Pathogens Including Sars-cov-mentioning
confidence: 84%
“…Small, non-enveloped viruses are considered to be less susceptible to microbicides, although these viruses display increased susceptibility to high pH, oxidizers such as sodium hypochlorite, activated hydrogen peroxide, alcohols, and a variety of microbicidal actives, relative to spores and protozoan cysts/oocysts. Mycobacteria, fungi, vegetative bacteria and enveloped viruses appear to be more susceptible to certain formulated microbicides, such as alcohols, oxidizers, quaternary ammonium compounds (QAC), and phenolics (e.g., p-chloro-m-xylenol) (Klein and Deforest, 1983;Sattar et al, 1989;McDonnell and Russell, 1999;Rabenau et al, 2005;Sattar 2007;Ijaz and Rubino, 2008;Geller et al, 2012;Cook et al, 2015;Cook et al, 2016;Cutts et al, 2018Cutts et al, , 2019Cutts et al, , 2020Rutala et al, 2019;Weber et al, 2019;Chin et al, 2020;Kampf et al, 2020;O'Donnell et al, 2020;O'Donnell et al, 2020;Senghore et al, 2020;Vaughan et al, 2020;Yu et al, 2020). A number of commercially available formulated microbicides (antiseptic liquid, hand sanitizers, liquid hand wash, bar soap, surface cleanser, disinfectant wipe, and disinfectant spray) have been evaluated for virucidal efficacy against SARS-CoV-2 , and as expected, were found to cause complete inactivation (3.0 to 4.7 log 10 ) within the 1 -5 minute contact times tested.…”
Section: Hierarchy Of Susceptibility Of Pathogens Including Sars-cov-mentioning
confidence: 99%
“…This enzyme preparation also inactivated the respiratory coronaviruses SARS-CoV-2 and HCoV-229E in vitro. Bacterial lipases from a Chromobacterium bacterium, named Chromobacterium antiviral effector-1 (CbAE-1) and CbAE-2, displayed a broad-spectrum invitro virucidal activity against dengue virus (DENV), Zika virus (ZIKV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), human immunodeficiency virus (HIV) and herpes simplex virus (HSV) [9]. In this paper we report the in vitro virucidal activity of commercially available enzyme preparations for SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%